A Comparative Study on Diet Supplementation with a Mixture of Herbal Plants and Dandelion as a Source of Prebiotics on the Performance of Broilers - Al-Kassi, Galib A.M.; Witwit, Noor M. (Pakistan Journal of Nutrition, 2009)
In this study a mixed herbal plants (Anise, Cinnamon, Peppermint) and Dandelion were added to the basal diet during the experimental period of 6 weeks. The study aimed to find out the effect of these treatments on productive and physiological traits of 200 broilers unsexed Hubbard chicks at the age of one day. These chicks were randomly divided into five groups equally (40 chicks each). Each group was subdivided into two equal subgroup, and fed with the following treatments. The first group (T1) was fed the basal diet and kept as a control, the second group (T2) was fed the same diet with adding 0.25% of mix herbal plants, where as the third group (T3) was fed the basal diet with adding 0.25% of Dandilion, while the fourth group (T4) was fed the basal diet with adding 0.50% from the mixed herbal plants and the fifth group (T5) was fed the same basal diet with adding 0.50% of Dandilion. The feeding period for all groups lasted for 42 days. The results appeared that there is an improvement in performance traits for all treated groups compared with the control group. However, the chicks fed with 0.25% Mix herbal plants performed better than those fed with 0.50% concerning weekly body weight gain, live body weight and mortality rate. However chicks fed with Dandelion (0.50%) were better in body weight gain, feed conversion ratio, live body weight and mortality rate than those fed with 0.25%. No significant effect was noticed on the addition of Mix herbal plants or Dandilion to the diet on blood traits and stress coefficient as compared with the control group. There was no significant effect on dressing percentage or edible giblet organs.